Proliferation of somatic embryos of Nothofagus alpina: effect of an exogen source of organic nitrogen - Castellanos, Hermes; Sánchez-Olate, Manuel; Wehenkel, Christian; Corral, Javier (Instituto de Ecología, A.C., 2016)
The effect of some sources of organic nitrogen such as hydrolyzed casein and the aminoacids L-glutamine and L-Serine were tested in the process of direct secondary somatic embryogenesis, in which somatic embryos of Nothofagus alpina -induced from isolated cotyledons of mature seeds- were used as explants. The highest percentages of direct secondary embryogenesis were obtained in BTM base medium plus MS vitamins, without plant growth regulators, and in this medium plus NAA, BAP and hydrolyzed casein. However, the fresh weight of the proliferated mass was greatest in the presence of an additional source of organic nitrogen. The highest average number of embryos per explant was also produced in the treatment with growth regulators and hydrolyzed casein, although the number was not significantly higher than in the L-Glutamine treatment, in which significantly less callus growth occurred. Alternate use of base medium and NAA, BAP and hydrolyzed casein medium during subculture enabled direct proliferation of the embryogenic culture, which remained stable for over two years and with a low incidence of callus.